PENDIDIKAN ISLAM DAN BAHASA ARAB MULTIKULTURAL DI MADRASAH - Rifa'i, Ahmad (IAIN Kediri, 2015)
Multicultural education means to learn about, prepare for, and celebrate cultural diversity. It requires changesÃ‚Â in school programs, policies and practices. Experts agreed that the content, structure and specific practices inÃ‚Â multicultural education are different according to the settings. This article will focus its discussion on multuralÃ‚Â education in teaching Arabic language. It found that multicultural education in teaching and learning ArabicÃ‚Â language can be implemented in maÃ¡Â¸Â¥Ã„Ârah al-arbÃ„ÂÃ¢â‚¬â„¢, including learning maÃ¡Â¸Â¥Ã„Ârah qirÃ„ÂÃ¢â‚¬â„¢ah, mahÃ„Ârah kalÃ„Âm,Ã‚Â mahÃ„Ârah kitÃ„Âbah, and mahÃ„Ârah istimÃ„ÂÃ¢â‚¬â„¢. In globalization era, problems of multiculturalism are inevitable,Ã‚Â including in learning Arabic because language is a human culture, which has different characteristics in termsÃ‚Â of race, ethnicity, religion, geography and language.Keywords: Pendidikan Multikultural, Bahasa Arab, MaÃ¡Â¸Â¥Ã„Ârah al-ArbÃ„ÂÃ¢â‚¬â„¢